2022
DOI: 10.1021/acsomega.1c06398
|View full text |Cite
|
Sign up to set email alerts
|

Gallium–Curcumin Nanoparticle Conjugates as an Antibacterial Agent against Pseudomonas aeruginosa: Synthesis and Characterization

Abstract: Combating antibiotic resistance has found great interest in the current clinical scenario. Pseudomonas aeruginosa , an opportunistic multidrug-resistant pathogen, is well known for its deadly role in hospital-acquired infections. Infections by P. aeruginosa are among the toughest to treat because of its intrinsic and acquired resistance to antibiotics. In this study, we project gallium–curcumin nanoparticle (GaCurNP) conjugates as a prospective candidate to fight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Finally, in the spectra of curcumin-loaded composites, characteristic peaks of curcumin can be clearly seen in the 1500–1600 cm –1 region where other components have no bands. The band at around 1501 cm –1 , ascribed to mixed C–O stretching, C–C–C bending, and C–C–O bending of curcumin, is significantly shifted to higher wavenumbers in composites, i.e., 1518 cm –1 in LVC and 1513 cm –1 in LSC. The possible formation of a complex through hydrogen bonding would explain the changes in the environment of these moieties .…”
Section: Resultsmentioning
confidence: 98%
“…Finally, in the spectra of curcumin-loaded composites, characteristic peaks of curcumin can be clearly seen in the 1500–1600 cm –1 region where other components have no bands. The band at around 1501 cm –1 , ascribed to mixed C–O stretching, C–C–C bending, and C–C–O bending of curcumin, is significantly shifted to higher wavenumbers in composites, i.e., 1518 cm –1 in LVC and 1513 cm –1 in LSC. The possible formation of a complex through hydrogen bonding would explain the changes in the environment of these moieties .…”
Section: Resultsmentioning
confidence: 98%
“…In this regard, curcuminoids, particularly CUR, have been complexed with various metals to achieve the desired synergistic effects. These formulations include curcumin–tannic acid-metal complexes (CUR-TA-Fe II and CUR-TA-Fe III) [ 101 ], curcumin–zinc oxide nanoparticles [ 102 ], and gallium–curcumin nanoparticles [ 103 ]. CUR has been reported to possess varying degrees of activity against the following viruses: high-risk human papillomaviruses, coxsackievirus, hepatitis C, herpes simplex virus type 1, influenza viruses (PR8, H1N1, and H6N1), and transmissible gastroenteritis virus [ 100 ].…”
Section: Notable Bioactivitiesmentioning
confidence: 99%
“…For bulky ligands (3,4,5,6,7), it was necessary to The stability constants of the complexes were calculated taking into account the possible complexes at the M:L 1:1, 1:2 and 1:3 molar ratios, but only for compounds 1 and 2 the refinements converged completely. For bulky ligands (3,4,5,6,7), it was necessary to exclude M:L 1:3 to reach convergence due to their steric hindrance that prevents the rearrangement of three ligands in the octahedral coordination sphere of Ga 3+ .…”
Section: Gallium Complexing Abilitymentioning
confidence: 99%
“…This limit could be overcome by designing new methods of administration or synthesizing novel daughter compounds with modified chemical structures. The first strategy allows stabilizing the molecule and increases its bioavailability by reducing its metabolism and increasing the retention time in the bloodstream; recently, many studies have reported on the encapsulation of CUR into nanocarriers (i.e., liposomes, engineered nanoparticles or exosomes, EXOs) with promising preclinical results [ 4 ] even for neurological pathologies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%